Microstrip Antenna Design With Circular Polarization Property For RF Energy Harvesting Application - Qasem Ahmed, Sharif Ahmed; Zakaria, Zahriladha; Husain, Mohd Nor; Abu, Maisarah (Research India Publications, 2016)
-